Laparoscopic Treatment with Single Incision for Varicocele in Children - Chen, Qimin; Zhong, Liang; Wu, Shaofeng; Sun, Yang; Ju, Guanqun; Sun, Jie (Urology Journal, 2015)
Purpose: Single port laparoscopic varicocelectomy had been introduced to treat varicocele. As the special instrument with three ports was a bit larger for children, a modified technique of single incision with two trocars was attempted in our department. The study was designed to compare it with the traditional laparoscopic method via three ports. Materials and Methods: Twelve boys of 14 varicoceles were admitted to accept laparoscopic varicocelectomy of single incision with two trocars. Thirty-two patients of 33 varicoceles with traditional three-port laparoscopy were reviewed as control. Data were collected to compare within the two groups. Results: All procedures were completed successfully in both groups. No significant difference in terms of patient’s age, operative time, blood loss, analgesic requirement, hospital stay or complication. Conclusion: The technique of laparoscopic varicocelectomy of single incision with two trocars was safe and effective. With the benefit of cosmetic appearance, it could be more satisfying.